On recursive expressions for statistics of decimated sequences - Pupeikis, Rimantas (Lietuvos matematikos rinkinys, 2021)
In what follows we introduce the recursive approach for calculating statistical moments of decimated realizations. We prove the corollaries referring to recursive calculation and present an example for any realization of 17 sample.